Extracellular vesicles isolation using size exclusion chromatography in microfluidics - Neo, Benjamin Wen Hao (Nanyang Technological University, 2021)
Extracellular vesicles (EVs) are nanosized (<1000nm) vesicles containing various biomolecules that are actively transported among various cellsthrough bodily fluids.They can be separated from high protein content bodily fluids using size exclusion chromatography (SEC) through differential elution time over a column of porous resin. However, the operation of SEC column remains batch mode and tedious, and there is a lack of simple and affordable process monitoring tool because the current HPLC/FPLC system is too expensive and bulky to be adopted in point-of-care settings. Herein, we developed a polymethyl methacrylate (PMMA) microfluidic SEC device with a non-chip passive cross junction inject or for EVs isolation. The device was fabricated using laser cutting of PMMA layers that were subsequently bonded together, with optimisation done to improve bonding strength and ensure leak-free fittings. It offers a simple sample injection mechanism using a three-way valve connected to a high resistive PDMS channel. Sample and sheath flows driven by syringe pumps allow continuous flow which avoids flow rate inconsistency due to manual sheath injection. Downstream detector can be directly connected to device’ outlet, which increases the flexibility for automation. The device was characterized using FITC BSA and 50nm beads to mimic separation of EVs from plasma protein, and an optimum flow rate of 10 μL/min was observed. In future work, we envision that the device can be with upstream plasma sample preparation tools or downstream EVs detection and assays to provide an integrated EVs isolation and on chip monitoring tool for clinical point-of-care EVs applications.